Physical activity and psychological well-being among physiotherapy degree students in UiTM Selangor, Puncak Alam Campus: A cross sectional study/ Wan Norhayati Wan Ab Rahman and Kartini Ilias - Wan Ab Rahman, Wan Norhayati; Ilias, Kartini (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
There is strong evidence that suggests the importance and benefits of physical activity for university students such as it enhances the psychological well-being of the students. The study objectives were (i) To identify the physical activity (PA) level among physiotherapy degree students. (ii) To determine the level of psychological well-being (PWB) among physiotherapy degree students. (iii) To examine the relationship between physical activity and psychological well-being among physiotherapy degree students in UiTM Puncak Alam Campus. Participants were 109 physiotherapy students (male n =4; female n = 105) age between 19 and 25 years old (M = 21.56 , SD = 1.512 ). Self-administered questionnaires which are International Physical Activity Questionnaire (IPAQ) and Psychological Well-Being Index (PGWBI) were used. 33.9% of the participants demonstrated low physical activity level, 34.9% and 31.2% showed moderate and high physical activity level respectively. 62.3% of the participants demonstrated severe and moderate psychological distress which show an alarming sign about students‟ well-being while 37.6% of the students showed being positive. A non-significant negative association between PA and PWB was found in the study. Physiotherapy degree students demonstrated a good level of physical activity. However, psychological distress among the students needs to be given attention.